2019
DOI: 10.1111/1754-9485.12896
|View full text |Cite
|
Sign up to set email alerts
|

Radiology teaching for interns: Experiences, current practice and suggestions for improvement

Abstract: Introduction: Junior doctors are typically responsible for requesting and interpreting diagnostic imaging studies. European studies have highlighted the paucity of radiology teaching leading to junior doctors feeling underprepared for clinical practice involving radiology. There is a lack of published data on the experiences of Australian medical students and junior doctors. This study aimed to describe the experiences of interns in Western Australia to establish whether they felt prepared for clinical practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…It may be in the best interests of radiologists to seek to educate referrers on the effect of clinical information on diagnostic performance, including the rationale behind providing high‐quality clinical information 38 . This need for further education is reflected in a recent study by Glenn‐Cox et al, 39 who identified that Australian junior doctors do not feel confident to request medical imaging tests accurately. With 66% of Australian junior doctors surveyed claiming to request imaging once a day or more frequently, 39 it is expected that development of criteria standards for clinical information when requesting medical imaging would be advantageous in improving the quality of the radiology report.…”
Section: Discussionmentioning
confidence: 99%
“…It may be in the best interests of radiologists to seek to educate referrers on the effect of clinical information on diagnostic performance, including the rationale behind providing high‐quality clinical information 38 . This need for further education is reflected in a recent study by Glenn‐Cox et al, 39 who identified that Australian junior doctors do not feel confident to request medical imaging tests accurately. With 66% of Australian junior doctors surveyed claiming to request imaging once a day or more frequently, 39 it is expected that development of criteria standards for clinical information when requesting medical imaging would be advantageous in improving the quality of the radiology report.…”
Section: Discussionmentioning
confidence: 99%
“…The survey found that the majority of undergraduate exposure to medical imaging was in an informal setting, with 52% reporting that the education provided did not adequately prepare them for post-graduate practice. 6 In an accompanying editorial, Mendelson and Taylor highlighted the frustrations they had encountered trying to implement a radiology curriculum into the local medical programme. Issues flagged included perceived insufficient teaching time available to accommodate a formalised radiology curriculum and resistance from non-radiology clinicians who considered themselves the preferred teachers of medical imaging within their own area of expertise.…”
Section: Building On Medical School Learningmentioning
confidence: 99%
“…It is also strongly encouraged that formalised medical imaging education should begin during medical school, with ongoing radiology education recognised as important for junior doctors, trainees, and specialists alike. 6,16 Even so, over the past 25 years, multiple studies have assessed the competency of junior doctors in interpreting plain radiographs and have consistently determined that general X-ray interpretation skills are suboptimal and argued that there is a need for improvement to the provision of medical imaging education beyond medical school. [17][18][19][20][21][22] Pre-speciality training junior doctors Independent surveys of recently graduated junior doctors in Australia, 6 Ireland 23 and the United Kingdom 24 found similar attitudes among participants towards the provision of diagnostic radiology education, as well as their preparedness for clinical practice.…”
Section: Medical Imaging Knowledge and Education For Different Non-radiologist Clinician Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…The article by Glenn‐Cox et al concerns the perception of Western Australian interns of their preparedness (or lack of it) for clinical practice by the radiology teaching they received at medical school and beyond, and raises issues upon which we wish to comment.…”
mentioning
confidence: 99%